A Note on Strongly Starlike Mappings in Several Complex Variables. (3rd March 2014) - Hamada, Hidetaka; Honda, Tatsuhiro; Kohr, Gabriela; Shon, Kwang Ho
Abstract : Let f be a normalized biholomorphic mapping on the Euclidean unit ball 𝔹 n in ℂ n and let α ∈ 0, 1 . In this paper, we will show that if f is strongly starlike of order α in the sense of Liczberski and Starkov, then it is also strongly starlike of order α in the sense of Kohr and Liczberski. We also give an example which shows that the converse of the above result does not hold in dimension n ≥ 2 .